2012
DOI: 10.3329/fmcj.v7i1.10292
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factor for Relapse in Childhood Nephrotic Syndrome - A Hospital Based Retrospective Study

Abstract: Nephrotic Syndrome (NS) is a common childhood illness characterized by massive proteinuria, hyperlipidemia, hypoalbuminemia & edema. NS is a disease of relapse and it is a major problem to manage the cases with frequent relapse. So it is very important to find out such children who are prone to develop frequent relapse. This retrospective study was conducted in the paediatric department of Dhaka Medical College Hospital (DMCH) from January to December 2005.Total 100 children with relapsed NS of them 50 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
17
5
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 9 publications
14
17
5
4
Order By: Relevance
“…Most of the children in our study belonged to 1-6 years (80%) while 20% of the children belonged to 6-12 years of age 14,15 . Male :Female ratio of the present study was 2:1, it was comparable to MN sarker et al,2005 study showed that 67% of children belonged to 2-6 years age group with male to female sex ratio roughly 2:1 7 . Subsequent relapse for Nephrotic Syndrome were commonly triggered by ARI(35%), other usual factor is UTI (21%).…”
Section: Discussionsupporting
confidence: 88%
“…Most of the children in our study belonged to 1-6 years (80%) while 20% of the children belonged to 6-12 years of age 14,15 . Male :Female ratio of the present study was 2:1, it was comparable to MN sarker et al,2005 study showed that 67% of children belonged to 2-6 years age group with male to female sex ratio roughly 2:1 7 . Subsequent relapse for Nephrotic Syndrome were commonly triggered by ARI(35%), other usual factor is UTI (21%).…”
Section: Discussionsupporting
confidence: 88%
“…Hepatomegaly was found in one case and 8% of the cases presented with Respiratory distress. Similar observations were made by Gulati S et al, 1995 9 , Sarker MN et al, 2005 10 . In the present study 76% of the cases were steroid responders and 24% of the cases were non-responder to steroid therapy.…”
supporting
confidence: 83%
“…Bazı çalışmalar, SR ya da SB nefrotik sendrom açısından yüksek riskle ilişkili hasta özelliklerini belirlemeye çalışmıştır, ama sonuçlar çelişkili bulunmuştur (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionunclassified